Cosmeceuticals Unveiled Innovation and Efficacy in Skincare Science - Mohd. Wasiullah; Piyush Yadav; Vikash Yadav; Ratnesh Yadav (Recent Trends in Cosmetics, 2024)
By combining the terms "Cosmeceuticals" and "pharmaceuticals," the phrase refers to goods that combine the medicinal benefits of pharmaceuticals with the aesthetic benefits of cosmetics. These innovative products do not strictly fall into the categories of either cosmetics or pharmaceuticals but serve as a bridge between the two, offering a unique combination of beauty enhancement and health improvement. Similar to pharmaceuticals, Cosmeceuticals contain active ingredients and compounds that are scientifically proven to deliver therapeutic outcomes. These products are formulated for various uses, including treatments for hair, skin, and nails, and are commonly available in topical forms such as lotions, creams, serums, gels, and other dermatological preparations. Unlike traditional cosmetics, which primarily focus on enhancing appearance, Cosmeceuticals go a step further by addressing underlying skin concerns and promoting overall health. They offer dual benefits: not only enhancing beauty and appearance but also providing targeted solutions for specific dermatological issues. Given their therapeutic nature, it is crucial to rigorously assess the safety and effectiveness of Cosmeceuticals through preclinical and clinical studies prior to their development and market release. This article explores some of the active ingredients that are currently incorporated into Cosmeceutical products, as well as potential candidates that could shape the future of this growing sector. It highlights the importance of ongoing research and innovation in creating Cosmeceutical formulations that not only improve the appearance of the skin, hair, and nails but also deliver long-term therapeutic benefits.
Keywords: cosmeceutical ingredients; cosmeceutical vehicles; cosmetics; current cosmeceutical compounds available; drugs